2006
DOI: 10.1002/bjs.5191
|View full text |Cite
|
Sign up to set email alerts
|

Duct-to-mucosa pancreaticogastrostomy is a safe anastomosis following pancreaticoduodenectomy

Abstract: Two-layered duct-to-mucosa pancreaticogastrostomy for restoration of pancreaticoenteric continuity after pancreaticoduodenectomy is associated with a low incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 23 publications
0
40
1
1
Order By: Relevance
“…Although the mortality rate of this reconstructive procedure following PD has decreased to 5% or less in recent years, the incidence of pancreatic fistulae, which is a leading cause of operative death, has been reported to remain in the range of 10-18% for the past 10 years [5][6][7][8][9][10]. On the other hand, an alternative pancreaticoenteric procedure, PG has been recently reported to have lower rates of pancreatic fistula (0-13%) and operative mortality (0-4.8%) [15][16][17][18][19][20][21][22][23][24][25]. To our knowledge, there have been three randomized controlled trials of PJ versus PG following PD reported in the previous English literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mortality rate of this reconstructive procedure following PD has decreased to 5% or less in recent years, the incidence of pancreatic fistulae, which is a leading cause of operative death, has been reported to remain in the range of 10-18% for the past 10 years [5][6][7][8][9][10]. On the other hand, an alternative pancreaticoenteric procedure, PG has been recently reported to have lower rates of pancreatic fistula (0-13%) and operative mortality (0-4.8%) [15][16][17][18][19][20][21][22][23][24][25]. To our knowledge, there have been three randomized controlled trials of PJ versus PG following PD reported in the previous English literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparative analyses of pancreaticoenterostomy in many studies have been performed with various surgical methods. In addition, some authors reported the superiority of PG with no control group included [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a small pancreatic duct size with a soft pancreas creates one of the technical hurdles to the completion of the anastomosis, and is known to be a risk factor for major leakage [3,[8][9][10][11][12][13] . Several methods have been advocated to reduce the occurrence of leakage [5,[14][15][16][17][18][19][20][21] , but the best technique is still a subject of debate [22][23][24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%